A critical role for IFN-β signaling for IFN-κ induction in keratinocytes - Xu, Bin; Musai, Jon; Tan, Yee Sun; Hile, Grace A.; Swindell, William R.; Klein, Benjamin; Qin, J. Tingting; Sarkar, Mrinal K.; Gudjonsson, Johann E.; Kahlenberg, J. Michelle (Frontiers in Lupus, 2024)
Background/Purpose: Cutaneous lupus erythematosus (CLE) affects up to 70% of patients with systemic lupus erythematosus (SLE), and type I interferons (IFNs) are important promoters of SLE and CLE. Our previous work identified IFN-kappa (IFN-κ), a keratinocyte-produced type I IFN, as upregulated in non-lesional and lesional lupus skin and as a critical regulator for enhanced UVB-mediated cell death in SLE keratinocytes. Importantly, the molecular mechanisms governing regulation of IFN-κ expression have been relatively unexplored. Thus, this study sought to identify critical regulators of IFN-κ and identified a novel role for IFN-beta (IFN-β). Methods: Human N/TERT keratinocytes were treated with the RNA mimic poly (I:C) or 50 mJ/cm2 ultraviolet B (UVB), followed by mRNA expression quantification by RT-qPCR in the presence or absence neutralizing antibody to the type I IFN receptor (IFNAR). IFNB and STAT1 knockout (KO) keratinocytes were generated using CRISPR/Cas9. Results: Time courses of poly(I:C) and UVB treatment revealed a differential expression of IFNB, which was upregulated between 3-6 hours and IFNK, which was upregulated 24 hours after stimulation. Intriguingly, only IFNK expression was substantially abrogated by neutralizing antibodies to IFNAR, suggesting that IFNK upregulation required type I IFN signaling for induction. Indeed, deletion of IFNB abrogated IFNK expression. Further exploration confirmed a role for type I IFN-triggered STAT1 activation. Conclusion: Collectively, our work describes a novel mechanistic paradigm in keratinocytes in which initial IFN-κ induction in response to poly(I:C) and UVB is IFNβ1-dependent, thus describing IFNK as both an IFN gene and an interferon-stimulated gene.